2011
DOI: 10.1021/es201444w
|View full text |Cite
|
Sign up to set email alerts
|

Do Temporal and Geographical Patterns of HBCD and PBDE Flame Retardants in U.S. Fish Reflect Evolving Industrial Usage?

Abstract: Polybrominated diphenyl ethers (PBDEs) and hexabromocyclododecane (HBCD) are common flame retardants in polymers and textiles. Recognition of the persistent, bioaccumulative, and toxic properties of PBDEs has prompted reductions in their use. In contrast, HBCD has received less scrutiny. The U.S has historically been a dominant BFR consumer. However, the few publications on HBCD in wildlife here suggest modest levels compared to Asian and European studies. In contrast, the HBCD concentrations we detected in U.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 31 publications
3
37
1
Order By: Relevance
“…The plecostomus have significant higher HBCD loading than the mud carp and nile tilapia (Table 1). HBCD levels in the Hyco River carp (mean 4640 ng/g lw) (Chen et al, 2011a), Belgian freshwater fish (median 4500 ng/g lw) (Roosens et al, 2008), and Swedish pike (6600 ng/g lw) (Sellstrom et al, 1998), were remarkably higher than that in the present study. The HBCD levels in the mud carp and the nile tilapia in the present study were comparable with those reported in fish from English lakes ) and Netherland Rivers (Morris et al, 2004) but the levels in the plecostomus in the present study were higher than those in English lakes and Netherland Rivers.…”
Section: Bioaccumulation Of Tbbpa and Hbcds In Fishcontrasting
confidence: 86%
“…The plecostomus have significant higher HBCD loading than the mud carp and nile tilapia (Table 1). HBCD levels in the Hyco River carp (mean 4640 ng/g lw) (Chen et al, 2011a), Belgian freshwater fish (median 4500 ng/g lw) (Roosens et al, 2008), and Swedish pike (6600 ng/g lw) (Sellstrom et al, 1998), were remarkably higher than that in the present study. The HBCD levels in the mud carp and the nile tilapia in the present study were comparable with those reported in fish from English lakes ) and Netherland Rivers (Morris et al, 2004) but the levels in the plecostomus in the present study were higher than those in English lakes and Netherland Rivers.…”
Section: Bioaccumulation Of Tbbpa and Hbcds In Fishcontrasting
confidence: 86%
“…As implemented in the U.S., Canada also supports the virtual voluntary elimination of DecaBDE by 2013 [29]. Industries are producing new brominated flame retardants which are now being measured in the environment [30,31] and show bioaccumulation in various organisms [32-34]. The new flame retardants products represent contaminants of emerging concerns and the persistence of the older ones such as PCBs and PBDEs are highly persistent in the environment and still an environmental problem particularly in aquatic systems where sediments are recognized as a sink for this class of contaminant.…”
Section: Reviewmentioning
confidence: 99%
“…Because levels of SHBCD in fish are expected to increase with growing demand for HBCD, it is important to monitor their concentration trends and fate of HBCD in the environment. For example, through comparing HBCD levels in fish from 1999 to 2002 and 2006 to 2007 collected from the Hyco, Dan, and Roanoke Rivers in southeastern Virginia, USA, and northeastern North Carolina, USA, Chen and coworkers [45] found an increasing trend for HBCD.…”
Section: Human Exposure To Hbcd Via Fish Consumptionmentioning
confidence: 99%